Evaluation of residual stress for multi-point repeated forming technology. (13th September 2020) - Shen, Wei; Yan, Renjun; Lin, Yue; Li, Peiyong
ABSTRACT: The processing of complex plates is increasingly used in large marine and hull structures, and multi-point pressure forming equipment has been developed to process complex hull plates. In order to improve forming accuracy and reduce residual stress, multi-point repeated forming technology has emerged with the development of processing technology. However, the bending problem of curved plates with initial curvature is too complicated for engineering applications for multiple bending processes, and the simplified theoretical model should be proposed to analyse the stress distribution of curved plates. Based on the theoretical analysis of the elastic–plastic bending of curved plates, an approximate method suitable for the stress analysis of repeated forming was proposed, and the formulas for calculating the residual stresses of curved plates were also deduced. Meanwhile, a procedure to simulate the residual stresses of curved plate with the multi-point repeated process was developed to verify the theoretical results.